2018
DOI: 10.1149/08614.0351ecst
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the Reduction of Rare Earth Metals in LiCl–KCl–CsCl Eutectic Melt

Abstract: Kinetic parameters of reduction of lanthanum, praseodymium and neodymium ions in the melts based on the ternary eutectic mixture of lithium, potassium and cesium chlorides were determined. The experiments were performed at 400–750 oC on a molybdenum working electrode employing chronopotentiometry. Potentials were measured vs. Ag/AgCl reference electrode. Reduction of Ln(III) ions to Ln(0) for all the elements studied occurred as a single stage process. The process was reversible and controlled by diffusion. Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The results obtained by CP and CV methods show a consistent trend, that is, the diffusion coefficients of La(III) are positively correlated with the temperature, which indicates that our work is reliable. Meanwhile, taking the diffusion coefficients calculated at 683 K in Table as an example, it can be found that it is one order of magnitude lower than that of La(III) at 683–813 K in LiCl–KCl. ,, The presence of Cs(I) has an obvious effect on the diffusion coefficients of La(III).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…The results obtained by CP and CV methods show a consistent trend, that is, the diffusion coefficients of La(III) are positively correlated with the temperature, which indicates that our work is reliable. Meanwhile, taking the diffusion coefficients calculated at 683 K in Table as an example, it can be found that it is one order of magnitude lower than that of La(III) at 683–813 K in LiCl–KCl. ,, The presence of Cs(I) has an obvious effect on the diffusion coefficients of La(III).…”
Section: Resultsmentioning
confidence: 97%
“…Meanwhile, taking the diffusion coefficients calculated at 683 K in Table 1 as an example, it can be found that it is one order of magnitude lower than that of La(III) at 683−813 K in LiCl−KCl. 46,67,68 The presence of Cs(I) has an obvious effect on the diffusion coefficients of La(III).…”
Section: ■ Results and Discussionmentioning
confidence: 99%